Under-floor Fixed Lifting Machine for Urban Rail Transit Maintenance - ZHANG Jin-li; ZHOU Sheng-ping; NIU Jun (机车电传动)
Taking maintenance of 6 sets for B type metro cars for instance, function, structure composition, technical parameters and technological innovation of metro vehicle under-floor fixed lifting machine were introduced. Test results showed that the lifting machine satisfied whole train synchronous-lifting maintenance requirement.